A novel fan beam and high gain antenna array for outdoor applications - Nguyễn, Trì (Journal of Military Science and Technology, 2023)
This paper introduces a novel high gain and wideband antenna array at 5 GHz for outdoor applications. The proposed array consists of a 2×9 elements planar array and a reflector. This antenna has a gain peak of 15.7 dBi and a bandwidth of 2 GHz from 4.0 GHz to 6.0 GHz. The angle coverage of 240° in the azimuth plane with gain 2 dBi higher. The total dimension of the antenna array is 31.5×13.4×1.2 cm3 which is fabricated on RO4003C substrate. The antenna has been fabricated and measured, the measurement and the simulation results are in good agreement.